Foreign arbitral award and international public policy. The challenge - Noriega Linares, Carmen María (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The judicial order of the TSJ of Madrid of 5th May 2022 allows to study several key aspects to grant or deny the recognition of the arbitral award. The fact that the respondent is absent from both the arbitration proceedings and the exequatur might seem to be of importance in order to trigger international public policy, but does it really matter? Perhaps what tips the balance in favor of refusal is the position attributed to the respondent and not its presence, or maybe there are other reaons. Therefore, it is necessary to be very clear about which laws are applicable to this procedure, what differentiates it from other similar ones and what the award must contain in order for international public policy to make its appearance or not. And all this is studied in this paper.